Study of the Prevalence, Causes and their Response to work Related Musculoskeletal Disorders among Saudi Therapists: Understanding the Impact of Musculoskeletal Injuries in the Saudi Physical Therapy Workforce (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Physiotherapists have a higher rate of musculoskeletal injuries due to their profession. Inorder to better understand the incidence, provocation, and management of musculoskeletal problems inthe Saudi physical therapy workforce, this research was done. Among the 110 Saudi physiotherapistssurveyed. Most Saudi physical therapists kept their jobs despite a high rate of musculoskeletal injuries.As a means of dealing with WRMD, people used coping mechanisms including changing their jobroutines.